Porphyrin(2.1.2.1) rhenium(I) complexes: Synthesis, structures, properties, and dipyrrin act as bipyridyl-like ligand. Issue 19 (17th December 2022) - Xue, Songlin; Lv, Xiaojuan; Liu, Ningchao; Morimoto, Hirofumi; Xiao, Bentian; Aratani, Naoki; Kuzuhara, Daiki; Yamada, Hiroko; Qiu, Fengxian
Abstract: Two new rhenium(I) porphyriniod complexes (H2 PY : 3, 3-rhenium(I) tricarbonyl chloride-(3 1 E, 3 2 Z, 7 1 E, 7 2 Z )-4, 8-bis(perfluorophenyl)-1 1 H, 3 2 H, 7 2 H -5 1 λ 2, 7 1 λ 4 -1, 5(2, 5), 3, 7(5, 2)-tetrapyrrola-2, 6(1, 2)-dibenzenacyclooctaphane, and H2 PZ : 3, 3-rhenium(I) tricarbonyl acetate-(3 1 E, 3 2 Z, 7 1 E, 7 2 Z )-4, 8-bis(perfluorophenyl)-1 1 H, 3 2 H, 7 2 H -5 1 λ 2, 7 1 λ 4 -1, 5(2, 5), 3, 7(5, 2)-tetrapyrrola-2, 6(1, 2)-dibenzenacyclooctaphane) containing two different Re(I)−N π-bonding networks were prepared from the saddle-shaped porphyrin(2.1.2.1) bearing pentafluorophenyl substituents at the two meso -positions (H2 Por : 3 1 E, 3 2 Z, 7 1 E, 7 2 Z )-4, 8-bis(perfluorophenyl)-1 1 H, 3 2 H, 5 1 H, 7 2 H -1, 5(2, 5), 3, 7(5, 2)-tetrapyrrola-2, 6(1, 2)-dibenzenacyclooctaphane). Despite the tetrapyrrolic nature of the porphyrin(2.1.2.1) scaffold, this is the first case of a pyrrole-based macrocycle which acts as a bipyridyl-like complexing ligand in the formation of an octahedral Re(I) complex. X-ray analysis and 1 H NMR studies show that both Re(I) complexes (H2 PY and H2 PZ ) consist of one octahedral Re(I) ion π-bonded to a dipyrrin unit and one protonated dipyrrin moiety linked together through o -phenylene bridges. This bonding behavior is compared to related metal complexes of porphyrin(2.1.2.1) macrocycles as well as other Re(I) porphyrins and demonstrates that the distorted conformation and, by virtue, the electronics of H2 Por serve as a novel platform for examining structure property relationships which differ than those of other related planar porphyrin macrocycles. Graphical Abstract: UF0001